Systematic review of surgical interventions for Crohn's anal fistula. Issue 3 (17th October 2017) - Lee, M J; Heywood, N; Adegbola, S; Tozer, P; Sahnan, K; Fearnhead, N S; Brown, S R; Hart, A; Lobo, A J; Sebastian, S; Sagar, P; Bach, S P; et al.
Abstract: Background: Anal fistula occurs in approximately one in three patients with Crohn's disease and is typically managed through a multimodal approach. The optimal surgical therapy is not yet clear. The aim of this systematic review was to identify and assess the literature on surgical treatments of Crohn's anal fistula. Methods: A systematic review was conducted that analysed studies relating to surgical treatment of Crohn's anal fistula published on MEDLINE, Embase and Cochrane databases between January 1995 and March 2016. Studies reporting specific outcomes of patients treated for Crohn's anal fistula were included. The primary outcome was fistula healing rate. Bias was assessed using the Cochrane ROBINS-I and ROB tool as appropriate. Results: A total of 1628 citations were reviewed. Sixty-three studies comprising 1584 patients were ultimately selected in the analyses. There was extensive reporting on the use of setons, advancement flaps and fistula plugs. Randomized trials were available only for stem cells and fistula plugs. There was inconsistency in outcome measures across studies, and a high degree of bias was noted. Conclusion: Data describing surgical intervention for Crohn's anal fistula are heterogeneous with a high degree of bias. There is a clear need for standardization of outcomes and description of study cohorts for better understanding of treatment options. Graphical Abstract: This study has systematically reviewed data on outcomes for surgery in Crohn's anal fistula. Studies have heterogenous outcomes precluding meta-analysis. This study highlights factors associated with poor generalizability of findings, which may be built upon by future researchers in this field. Limited evidence for the preferred surgical approach